2005
DOI: 10.1007/s00421-005-1394-4
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of short calf muscle-tendon units of older women: effects of slow and fast passive dorsiflexion stretches in vivo

Abstract: Changes in connective tissues of the skeletal muscle-tendon unit (MTU) of aging animal muscles have been associated with increased passive viscoelastic properties. This study examined whether similar changes in the viscoelastic properties were present in short calf MTUs of older women in vivo. Fifteen women 68-87 years of age with short calf MTUs, as represented by limited active dorsiflexion (DF) range of motion (ROM) of < or =5 degrees, and 15 women 20-26 years of age without decreased DF ROM participated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 45 publications
7
58
2
3
Order By: Relevance
“…At this ankle joint angle, the passive joint moment can achieve values between 20 and 30·Nm (Riener and Edrich, 1999;Mullaney et al, 2006). Moreover, due to the viscoelastic behaviour of the connective tissues, in a dorsiflexed position the passive ankle joint moments may be higher in a dynamic condition (Gajdosik et al, 2005) such as walking. Studies examining the EMG activity of the triceps surae muscles while walking reported values between 19 and 42% of the maximal isometric EMG value (Ericson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…At this ankle joint angle, the passive joint moment can achieve values between 20 and 30·Nm (Riener and Edrich, 1999;Mullaney et al, 2006). Moreover, due to the viscoelastic behaviour of the connective tissues, in a dorsiflexed position the passive ankle joint moments may be higher in a dynamic condition (Gajdosik et al, 2005) such as walking. Studies examining the EMG activity of the triceps surae muscles while walking reported values between 19 and 42% of the maximal isometric EMG value (Ericson et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Computerized dynamometers have often been used in passive mode to assess passive musculo-articular properties [7][8][9][10][11][12][13][14][15][16][17][18]. However, to our knowledge, the accuracy of the measurements provided by dynamometers under these conditions has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, our results demonstrated that the Biodex system 3 pro performed reliable and valid torque measurements during passive stretching at different velocities. This tool would be suitable to perform clinical studies, for instance, to assess the effects of ageing [12] or spasticity [13][14][15][16][17][18] on passive musculo-articular properties determined at different angular velocities.…”
Section: Reliability and Validity Of Torque Measurementsmentioning
confidence: 99%
See 2 more Smart Citations